Identifikasi Aspek Pengembangan Kawasan Konservasi Penyu Pantai Trisik sebagai Wadah Wisata Edukasi Penyu di Kulonprogo - Darmarani, Chiquita; Muqoffa, Mohamad; Mustaqimah, Ummul (ARSITEKTURA, 2020)
Sea turtle is classified into endangered animal. One of the areas which is designated as sea turtle conservation area in Indonesia is located at Trisik Beach, Kulonprogo. The government’s sea turtle conservation effort is supported by the Penyu Abadi Conservation Group, that has been carrying out sea turtle conservation activities since 2004. By the development of this conservation activities, in 2018, Dinas Pariwisata Daerah Istimewa Yogyakarta finally planned a development program for the attractiveness of sea turtle conservation areas on the southern coast of Yogyakarta, including Trisik Beach. One form of developing the attraction of conservation areas is sea turtle educational tourism object. The development of a sea turtle conservation area into a tourist attraction for sea turtle education should not disturb the balance of the natural ecosystem of Trisik Beach sea turtle nesting.  Therefore, the problem formulated in this research is what aspects must be fulfilled to realize the recreational sea turtle educational tourism, by paying attention to its main function as a supporter of regional marine conservation activities. The problem solving is done by applying the applied research methods, namely the type of research that aims to provide practical solutions for the problem. This research produced some guidelines that can be implemented in the development of Trisik Beach sea turtle conservation area, to be the basis for future development planning.